PELAYANAN PUBLIK YANG BERPIHAK PADA KESEJAHTERAAN MASYARAKAT - Sumaryanto - - (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2008)
ABSTRACT Quality of public service influenced by Some dominant factor among others is public policy, covering finance aspect, technological and good human resource being and also nature and also organization, environment and characteristic society itself, including in it mount education, mount earnings, norm, political, free mass media, and governmental control to public service. Key from make-up of the public service quality is how to improve position balance bargain between various stakeholders, because to increase efficiency require action from various corner. Keywords: public service, society prosperity, public policy